Effect of Bacillus thuringiensis based-products on rats - Mohd Najib Ahmad (2020)
Registration of pesticides with the National Pesticide Board must undergo laboratory testing for short-term and long-term health effects. Laboratory animals such as rats are purposely fed with high doses of the pesticide to cause toxic effects. The objectives of this study are to investigate the effect of Bacillus thuringiensis-based Bafog-1 (S) and Ecobac-1 (EC) against Sprague Dawley rats, to assess the toxicity of these Bt products. The acute oral and acute dermal toxicity studies were conducted according to OECD (Organisation for Economic Co-operation and Development) Guideline for Testing of Chemicals 425 (2001) and 402 (1987), respectively. The oral LD50 of Ecobac-1 (EC) and Bafog-1 (S) on female rats is more than 5000 mg kg-1, when administered orally with dose of 175 mg kg-1, respectively. Correspondingly, the LD50 for dermal administration of both Bt products is more than 2000 mg kg-1 for both male and female rats. There was no toxic symptom observed during the two weeks observation period in male and female rats. Post-mortem of the dermally treated animals at the end of the experiment did not show changes or adverse effect in the rats’ internal organs, indicating these two products are non-toxic to rats. Bt as an environmental-friendly microbial insecticide is generally not toxic to human, domestic animals and vertebrates.